A method for preparing high-grade pyrophyllite white porcelain
By using chloroplast as a base material and adjusting the binding performance of the blank glaze, the problem of insufficient thermal expansion coefficients of high -temperature white porcelain body is solved, and the high temperature stability and rapid firing of white porcelain are achieved, which improves the quality of the product and reduces energy consumption.
Patent Information
- Application Number
- CN202410107277.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-01-26
AI Technical Summary
Due to the defect in the thermal expansion coefficient of the blank, existing high-temperature white porcelain cannot be used for secondary firing on transparent glaze, and the blank glaze is poorly adaptable, which affects the rapid firing of the kiln.
Pyrophyllite is used as the base material to produce high-grade white porcelain. By adjusting the bonding performance between the base and glaze, the expansion coefficient of the base is slightly greater than that of the glaze, improving the adaptability of the base glaze, and utilizing the low structural water and permanent lines of pyrophyllite. Expansion properties reduce deformation and shrinkage during firing.
It achieves high-temperature stability and rapid firing of white porcelain, improves product quality, reduces energy consumption, and solves the problem that conventional high-temperature white porcelain cannot be fired twice.
Smart Images

Figure CN118145954B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pyrophyllite high-grade white porcelain, in particular to a preparation method of pyrophyllite high-grade white porcelain. Background Art
[0002] As people's living standards continue to improve, the requirements for ceramic materials are getting higher and higher. People not only require perfect appearance, but also require internal performance and other aspects. White porcelain is a kind of porcelain and one of the important representatives of ancient Chinese civilization. It was originally made for royal use, but now it has spread all over the world. The production process of white porcelain requires multiple links, including raw material screening, mud making, molding, trimming, drying, firing, decoration, etc.
[0003] Pyrophyllite crystals are mainly monoclinic, usually in the form of flaky, radial aggregates with pearly halos or cryptocrystalline flaky dense blocks, generally white with a slight yellowish or greenish tint and white streaks, ranging from glassy luster, pearly luster, waxy luster to dull, soft and slippery. There is a balanced endothermic reaction valley at 600-700°C, and no exothermic reaction peak appears at 1000°C. This is because the structure of pyrophyllite is not destroyed after the dehydration reaction, and no new crystallization and combination occur. Ores used in general industry contain more than 50% pyrophyllite, and the ore types include quartz-pyrophyllite, kaolin-pyrophyllite, diaspore-pyrophyllite, sericite-pyrophyllite and relatively pure pyrophyllite.
[0004] According to their genesis, my country's pyrophyllite deposits can be divided into two categories: hydrothermal and metamorphic. It is estimated that by 2000, my country's total demand for pyrophyllite reached 900,000 tons, with an average annual increase of 5.8% to 6.8%. The main deposits are: the Emei ore field in Shoushan, Fuzhou, Fujian, the Longmen ore field in Xiagaozhou, Shangrao, Jiangxi, the kaolinite deposit of Duqi pyrophyllite in Linhai, Zhejiang, and the Mentougou pyrophyllite deposit in Beijing. The Mentougou pyrophyllite deposit in Beijing is a mineralized hydrothermal fissure filling-an altered deposit, acidic pyroclastic rock or aluminum-rich ore. In the above-mentioned mineralization structural background, especially in the developed fault structure, the main mineralization is hydrothermal filling, accompanied by altered pyrophyllite, mercury, and alunite in the near-ore surrounding rocks, followed by pyrite, quartz, and a small amount of kyanite and sillimanite.
[0005] Existing white porcelain is usually fired once at around 1300°C to obtain a daily-use porcelain with high whiteness and transparency. However, due to the defects of the thermal expansion coefficient of the conventional high-temperature white porcelain body itself, it is impossible to apply transparent glaze for secondary firing, and the adaptability of the body and glaze is poor, which affects the rapid firing of the white porcelain kiln.
[0006] Therefore, the present invention provides a method for preparing high-grade pyrophyllite white porcelain, which is used to solve the above-mentioned related technical problems. Summary of the invention
[0007] The object of the present invention is to provide a method for preparing high-grade white porcelain made of pyrophyllite, so as to solve the problem that the conventional high-temperature white porcelain in the prior art cannot be coated with transparent glaze for secondary firing due to the defect of the thermal expansion coefficient of the body itself, and the body glaze has poor adaptability, which affects the rapid firing of the white porcelain kiln; the high-grade white porcelain is produced by using pyrophyllite as a base material, because the pyrophyllite has less structural water and relatively stable water content, and the pyrophyllite also has permanent linear expansion and good reheating stability, therefore, the white porcelain produced by using pyrophyllite as a raw material is easy to burn. It has small shape, good thermal stability, high content of crystalline quartz and large expansion coefficient. The characteristics of pyrophyllite body can be used to adjust the bonding performance between the body and glaze in the opposite way, so that the expansion coefficient of the body in each temperature zone is slightly larger than the expansion coefficient of the glaze. Therefore, the body and glaze have good adaptability. Pyrophyllite contains less structural water, and the dehydration process is slow, and the shrinkage during the firing process is small, which is conducive to the rapid firing of the kiln, improves the product quality of ceramics and saves energy and reduces consumption. It solves the problem that conventional high-temperature white porcelain cannot be coated with transparent glaze for secondary firing due to the defects of its body's own thermal expansion coefficient.
[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing high-grade pyrophyllite white porcelain, wherein the raw materials for preparing the white porcelain include blank and glaze:
[0009] The blank formulation is composed of the following by weight: 10-20 parts of black mud, 15-20 parts of Datong soil, 8-10 parts of feldspar, 20-30 parts of pyrophyllite, 8-10 parts of quartz, 10-15 parts of panning mud, 15-25 parts of Longyan soil, 1-4 parts of bone meal and 1-3 parts of talc;
[0010] The glaze formula is composed of the following by weight: 5 to 10 parts of talc, 30 to 50 parts of feldspar, 15 to 30 parts of quartz, 10 to 15 parts of limestone, 4 to 10 parts of Suzhou soil, 1 to 15 parts of white porcelain powder, 1 to 3 parts of zircon and 2 to 5 parts of zinc oxide;
[0011] The preparation method of the white porcelain comprises the following steps:
[0012] S1. Prepare blanks according to formula components;
[0013] S2, preparing glaze according to the formula components;
[0014] S3, pressing or injection molding the prepared blank to obtain a blank;
[0015] S4, subjecting the obtained green body to high temperature shaping bisque firing at 1300-1350° C., water-polishing, air-drying, and applying glaze to obtain a glaze green body after bisque firing;
[0016] S5. The obtained glaze blank is fired for a second time at 1200-1350°C, and white porcelain is obtained after cooling.
[0017] The present invention is further configured as follows: the chemical components of the blank include 50 to 70 parts by weight of SiO 2 , 20~40 parts Al 2 O 3 , 0.1~1.4 parts Fe 2 O 3 , 0.1-0.5 parts TiO 2 , 1.2-1.8 parts CaO, 0.3-0.7 parts MgO, 0.3-12 parts K 2 O, 0.2 to 1.8 parts of Na 2 O, 0.1~1.5 parts P 2 O 5 and 1 to 20 portions of IL.
[0018] The present invention is further configured as follows: the chemical components of the glaze include 60 to 90 parts by weight of SiO 2 , 1 to 20 parts Al 2 O 3 , 0.1~1.2 parts Fe 2 O 3 , 0.2-52 parts CaO, 0.3-30 parts MgO, 0.1-3 parts TiO 2 , 0.1-15 parts KNaO, 1-60 parts ZrO 2 , 1 to 7 portions K 2 O, 0.2~1.5 parts Na 2 O, 1 to 5 parts of ZnO and 1 to 3 parts of IL.
[0019] The present invention is further configured as follows: in step S1, preparing the blank according to the formula components comprises the following steps:
[0020] S11, crushing the materials such as black mud, Datong soil and feldspar, and batching the materials for preparing the blank according to the formula ratio;
[0021] S12, adding the ingredients in step S11 into a rapid ball mill for mixing and ball milling for 24-26 hours, and the ratio of ingredients: ball: water is 1:1.8:0.8, and the prepared raw materials are crushed to make them into fine powder;
[0022] S13, sieving the fine powder raw material with a magnetic separator to remove iron, and then mixing it with water and repeatedly stirring until a uniform slurry is formed;
[0023] S14, filtering and kneading the mud and then aging it for later use, the mud fineness is 0.02-0.03% of the residue on the 10,000-hole sieve, and the moisture content of the mud is 23-25%.
[0024] The present invention is further configured as follows: in step S2, the glaze is prepared according to the formula components, comprising the following steps:
[0025] S21, mixing the raw materials for preparing the glaze according to the formula ratio, and crushing and beating the ingredients to obtain a mixture;
[0026] S22, adding the mixed material in step S21 into a rapid ball mill for mixing and ball milling for 20 hours, and adding an appropriate amount of water, with the ratio of mixed material: ball: water being 1:1.5:0.6, to obtain a ball mill material;
[0027] S23, adding water to the ball mill to prepare a glaze.
[0028] The present invention is further configured as follows: in step S3, the clay material in step S14 is poured into a shaping mold, and is formed into a green body by vibration and compression, and then the formed green body is trimmed and dried, wherein the trimming is to remove unevenness and defects on the surface of the green body, and the drying is to remove excess moisture.
[0029] The present invention is further configured as follows: in step S4, the method of applying the glaze can be dipping or spraying, and the glazing specific gravity during dipping is 1.36-1.40, and the glazing specific gravity during spraying is 1.55-1.60, and the dried material components are added into a rapid ball mill according to the ratio for mixed ball milling, and the glaze layer thickness is 0.3-0.4mm.
[0030] The present invention is further configured as follows: in step S5, the secondary firing is performed by placing the glaze blank obtained in step S4 in a 74m high-temperature tunnel kiln under oxidizing atmosphere conditions to melt the glaze and adhere to the surface of the porcelain, and the maximum firing temperature is 1310°C, the firing cycle is 16h, and the insulation time is 100min.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] In the present invention, pyrophyllite is used as a base material to produce high-grade white porcelain. Since pyrophyllite has less structural water and relatively stable water content, pyrophyllite also has permanent linear expansion and good reheating stability, the white porcelain produced by using pyrophyllite as a raw material has small deformation, good thermal stability, high crystalline quartz content and large expansion coefficient. The characteristics of the pyrophyllite blank can be used to adjust the bonding performance between the blank and the glaze through the opposite way, so that the expansion coefficient of the blank in each temperature zone is slightly greater than the expansion coefficient of the glaze, so the blank and the glaze have good adaptability. The pyrophyllite contains less structural water (5%), and the dehydration process is slow (550°C-900°C), and the shrinkage during the firing process is small, which is conducive to the rapid firing of the kiln, improves the product quality of the ceramic, saves energy and reduces consumption, and solves the problem that the conventional high-temperature white porcelain cannot be coated with transparent glaze for secondary firing due to the defect of the thermal expansion coefficient of the blank itself. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention is a flow chart of the preparation method of the pyrophyllite high-grade white porcelain formula. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the implementation regulations described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing high-grade pyrophyllite white porcelain, wherein the raw materials for preparing the white porcelain include blank and glaze:
[0037] The blank formulation is composed of the following by weight: 12 parts of black mud, 17 parts of Datong soil, 9 parts of feldspar, 25 parts of pyrophyllite, 9 parts of quartz, 12 parts of panning mud, 20 parts of Longyan soil, 2 parts of bone meal and 1 part of talc;
[0038] The chemical composition of the blank by weight includes: 64 parts SiO 2 , 22 parts Al 2 O 3 , 0.3 parts Fe 2 O 3 , 0.2 parts TiO 2 , 1.5 parts CaO, 0.7 parts MgO, 1.8 parts K 2 O. 1 part Na 2 O, 0.8 parts P 2 O 5 and 8 ILs;
[0039] The glaze formula is composed of the following by weight: 7 parts of talc, 45 parts of feldspar, 25 parts of quartz, 12 parts of limestone, 7 parts of Suzhou soil, 6 parts of white porcelain powder, 2 parts of zircon and 5 parts of zinc oxide;
[0040] The chemical composition of the glaze by weight includes: 61 parts SiO 2 , 12 parts Al 2 O 3 , 0.1 parts Fe 2 O 3 , 7 parts CaO, 2 parts MgO, 0.1 parts TiO 2 , 3 parts KNaO, 1 part ZrO 2 , 5 K 2 O. 1 part Na 2 O, 5 parts ZnO and 2 parts IL;
[0041] The method for preparing white porcelain comprises the following steps:
[0042] S1. Preparing blanks according to the formula components, including the following steps:
[0043] S11, crushing the materials such as black mud, Datong soil and feldspar, and batching the materials for preparing the blank according to the formula ratio;
[0044] S12, adding the ingredients in step S11 into a rapid ball mill for mixing and ball milling for 25 hours, and the ratio of ingredients: ball: water is 1:1.8:0.8, and the prepared raw materials are crushed to make them into fine powder;
[0045] S13, sieving the fine powder raw material with a magnetic separator to remove iron, and then mixing it with water and repeatedly stirring until a uniform slurry is formed;
[0046] S14, filtering and kneading the mud and then aging it for later use, the mud fineness is 0.03% of the sieve residue of 10,000 mesh sieve, and the moisture content of the mud is 24%;
[0047] S2, preparing glaze according to the formula components, including the following steps:
[0048] S21, mixing the raw materials for preparing the glaze according to the formula ratio, and crushing and beating the ingredients to obtain a mixture;
[0049] S22, adding the mixed material in step S21 into a rapid ball mill for mixing and ball milling for 20 hours, and adding an appropriate amount of water, with the ratio of mixed material: ball: water being 1:1.5:0.6, to obtain a ball mill material;
[0050] S23, adding water to the ball mill to prepare a glaze;
[0051] S3, pressing or slip-casting the prepared blank to obtain a blank; pouring the clay material in step S14 into a shaping mold, and forming it into a blank by vibration and compression, and then trimming and drying the formed blank, trimming to remove unevenness and defects on the surface of the blank, and drying to remove excess moisture;
[0052] S4, the obtained body is subjected to high temperature shaping bisque firing at 1300°C, and after bisque firing, it is water-polished, air-dried, and glazed to obtain a glazed body; the method of applying the glaze can be glazing or spraying, and the glazing specific gravity during glazing is 1.36, and the glazing specific gravity during spraying is 1.55, and the dried materials are added into a rapid ball mill according to the proportion for mixing and ball milling, and the thickness of the glaze layer is 0.4mm;
[0053] S5, the obtained glaze blank is subjected to secondary firing at 1300°C, and white porcelain is obtained after cooling; secondary firing, the glaze blank obtained in step S4 is placed in a 74m high-temperature tunnel kiln and fired under oxidizing atmosphere conditions, so that the glaze melts and adheres to the surface of the porcelain, and the maximum firing temperature is 1310°C, the firing cycle is 16h, and the insulation time is 100min.
[0054] Example 2
[0055] This embodiment provides a method for preparing high-grade pyrophyllite white porcelain, wherein the raw materials for preparing the white porcelain include blank and glaze:
[0056] The blank formulation is composed of the following by weight: 10 parts of black mud, 15 parts of Datong soil, 9 parts of feldspar, 20 parts of pyrophyllite, 8 parts of quartz, 10 parts of panning mud, 15 parts of Longyan soil, 1 part of bone meal and 1 part of talc;
[0057] The chemical composition of the blank by weight includes: 50 parts SiO 2 , 20 parts Al 2 O 3 , 0.1 parts Fe 2 O 3 , 0.1 parts TiO 2 , 1.2 parts CaO, 0.3 parts MgO, 0.3 parts K 2 O, 0.2 parts Na 2 O, 0.1 part P 2 O 5 and 1 IL;
[0058] The glaze formula is composed of the following by weight: 5 parts of talc, 30 parts of feldspar, 15 parts of quartz, 10 parts of limestone, 4 parts of Suzhou soil, 1 part of white porcelain powder, 1 part of zircon and 2 parts of zinc oxide;
[0059] The chemical components of the glaze by weight include: 60 parts SiO 2 , 1 part Al 2 O 3 , 0.1 parts Fe 2 O 3 , 0.2 parts CaO, 0.3 parts MgO, 0.1 parts TiO 2 , 0.1 part KNaO, 1 part ZrO 2 , 1K 2 O, 0.2 parts Na 2 O, 1 part ZnO and 1 part IL.
[0060] Example 3
[0061] This embodiment provides a method for preparing high-grade pyrophyllite white porcelain, wherein the raw materials for preparing the white porcelain include blank and glaze:
[0062] The blank formulation is composed of the following by weight: 20 parts of black mud, 20 parts of Datong soil, 10 parts of feldspar, 30 parts of pyrophyllite, 10 parts of quartz, 15 parts of panning mud, 25 parts of Longyan soil, 4 parts of bone meal and 3 parts of talc;
[0063] The chemical composition of the blank by weight includes: 70 parts SiO 2 、40 parts Al 2 O 3 , 1.4 parts Fe 2 O 3 , 0.5 parts TiO 2 , 1.8 parts CaO, 0.7 parts MgO, 12 parts K 2 O, 1.8 parts Na 2 O, 1.5 parts P 2 O 5 and 20 ILs;
[0064] The glaze formula is composed of the following by weight: 10 parts of talc, 50 parts of feldspar, 30 parts of quartz, 15 parts of limestone, 10 parts of Suzhou soil, 15 parts of white porcelain powder, 3 parts of zircon and 5 parts of zinc oxide;
[0065] The chemical components of the glaze by weight include: 90 parts SiO 2 , 20 parts Al 2 O 3 , 1.2 parts Fe 2 O 3 , 52 parts CaO, 30 parts MgO, 3 parts TiO 2 , 15 parts KNaO, 60 parts ZrO 2 , 7 portions K 2 O, 1.5 parts Na 2 O, 5 parts of ZnO and 3 parts of IL.
[0066] Proportion test
[0067] The proportion test of the blank and glaze was carried out respectively. The chemical composition of several main raw materials in the blank formula is shown in Table 1, and the chemical composition of several main raw materials in the glaze formula is shown in Table 2:
[0068] Table 1 Chemical composition of main raw materials in blank formulation
[0069]
[0070] Table 2 Chemical composition of main raw materials in glaze formula
[0071]
[0072] After multiple proportion tests of blank formulas, the following formula composition was determined: 8 parts of feldspar, 8 parts of quartz, 20 parts of Longyan soil, 21 parts of pyrophyllite, 10 parts of black mud, 20 parts of Datong soil, 10 parts of panning mud, 2 parts of bone meal, and 1 part of talc. The chemical composition of blank L-5# is shown in Table 3:
[0073] Table 3 Chemical composition of the blank
[0074]
[0075] In the glaze ratio test, high-temperature raw transparent glaze was used. Through comparative tests on multiple formulas, it was determined that the transparent glaze formula with good performance and matching with L-5# body was T-3#. After firing at 1300℃, a product with good sintering performance, high whiteness and smooth glaze surface was obtained. The chemical composition of the glaze is shown in Table 4:
[0076] Table 4 Chemical composition of glaze
[0077]
[0078] There are many factors that affect the quality of the glaze. In order to find out the main components and addition amounts that affect the quality of the glaze quickly and accurately with as few tests as possible, the experiment is planned to use a multi-factor orthogonal test method to arrange the experiment (the quantitative components are: 40 parts of feldspar, 20 parts of quartz, 4 parts of Suzhou soil, and 11 parts of white porcelain powder). The factor levels are shown in Table 5, and the test results are shown in Table 6:
[0079] Table 5 Consideration factors and levels
[0080]
[0081]
[0082] Table 6 Test results of orthogonal array
[0083]
[0084] Analysis of test results: From the results of the orthogonal test, it can be seen that the main components affecting the glaze quality are limestone, talc, zinc oxide and zircon, and the optimal addition amounts are 12 parts of limestone, 6 parts of talc, 5 parts of zinc oxide and 2 parts of zircon. The chemical composition of the glaze measured according to the optimal ratio is shown in Table 4. According to the test results, taking into account factors such as cost, the glaze formula was finally determined as follows: 40 parts of feldspar, 20 parts of quartz, 12 parts of limestone, 6 parts of talc, 4 parts of Suzhou soil, 5 parts of zinc oxide, 11 parts of white porcelain powder and 2 parts of zircon.
[0085] Comparative Example 1
[0086] The pyrophyllite high-grade white porcelain and its preparation method provided in this embodiment are substantially the same as those in Embodiment 1, the main difference being that pyrophyllite is not added.
[0087] Comparative Example 2
[0088] The pyrophyllite high-grade white porcelain and its preparation method provided in this embodiment are substantially the same as those in Embodiment 1, the main difference being that no panning mud is added.
[0089] Comparative Example 3
[0090] The pyrophyllite high-grade white porcelain and its preparation method provided in this embodiment are substantially the same as those in Embodiment 1, the main difference being that no black mud is added.
[0091] Performance Testing
[0092] The blank and glaze prepared by the ratio test are taken as the test group, and the blanks and glazes prepared by Examples 1 to 3, Comparative Examples 1 to 3 and the test group are taken, and the relevant properties of the prepared ceramic products (white porcelain) are tested, and the testing method is as follows: the thermal stability of the product is tested according to the GB / T3298-2008 daily-use ceramic thermal shock resistance test method, the whiteness test is performed according to the GB / T1503-2011 daily-use ceramic whiteness determination method, the gloss test is performed according to the GB / 3295-2011 daily-use ceramic gloss test method, and the water absorption of the product is tested according to the GB / T3299-2011 daily-use ceramic water absorption test method; the test results are recorded in Table 7;
[0093] Table 7 Ceramic test table
[0094]
[0095] By analyzing the relevant data in the above table, it can be seen that in the present invention, as shown in the data of the test group in Table 7, the whiteness of the prepared white porcelain is 74%, the thermal stability is passed, the glossiness is 115.8, and the water absorption rate is 0.2%. The high-grade white porcelain is produced by using pyrophyllite as the base material. Since the structural water of pyrophyllite is less and the water content is relatively stable, the pyrophyllite also has permanent linear expansion and good reheating stability. Therefore, the white porcelain produced by using pyrophyllite as the raw material has small deformation, good thermal stability, high crystalline quartz content, and expansion coefficient. The pyrophyllite body has a relatively large thermal expansion coefficient, and the pyrophyllite body has a relatively large thermal expansion coefficient. The ...
[0096] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing high-grade pyrophyllite white porcelain, characterized in that: The raw materials for preparing the white porcelain include blank and glaze: The blank formula is composed of the following by weight: 10-20 parts of black mud, 15-20 parts of Datong soil, 8-10 parts of feldspar, 20-30 parts of pyrophyllite, 8-10 parts of quartz, 10-15 parts of elution mud, 15-25 parts of Longyan soil, 1-4 parts of bone meal and 1-3 parts of talc. The chemical components of the blank by weight include: 50-70 parts of SiO2, 20-40 parts of Al2O3, 0.1-1.4 parts of Fe2O3, 0.1-0.5 parts of TiO2, 1.2-1.8 parts of CaO, 0.3-0.7 parts of MgO, 0.3-12 parts of K2O, 0.2-1.8 parts of Na2O, 0.1-1.5 parts of P2O5 and 1-20 parts of IL; The glaze formula is composed of the following by weight: 5-10 parts of talc, 30-50 parts of feldspar, 15-30 parts of quartz, 10-15 parts of limestone, 4-10 parts of Suzhou soil, 1-15 parts of white porcelain powder, 1-3 parts of zircon and 2-5 parts of zinc oxide. The chemical components of the glaze by weight include: 60-90 parts of SiO2, 1-20 parts of Al2O3, 0.1-1.2 parts of Fe2O3, 0.2-52 parts of CaO, 0.3-30 parts of MgO, 0.1-3 parts of TiO2, 0.1-15 parts of KNaO, 1-60 parts of ZrO2, 1-7 parts of K2O, 0.2-1.5 parts of Na2O, 1-5 parts of ZnO and 1-3 parts of IL; The preparation method of the white porcelain comprises the following steps: S1. Prepare blanks according to formula components; S2, preparing glaze according to the formula components; S3, pressing or slip-casting the prepared blank to obtain a blank; S4, subjecting the obtained green body to high temperature shaping bisque firing at 1300-1350° C., water-polishing, air-drying, and applying glaze to obtain a glaze green body after bisque firing; S5. The obtained glaze blank is fired for a second time at 1200-1350°C, and white porcelain is obtained after cooling.
2. The method for preparing a pyrophyllite high-grade white porcelain according to claim 1, characterized in that: In step S1, the blank is prepared according to the recipe components, including the following steps: S11, crushing the materials such as black mud, Datong soil and feldspar, and batching the materials for preparing the blank according to the formula ratio; S12, adding the ingredients in step S11 into a rapid ball mill for mixing and ball milling for 24-26 hours, and the ratio of ingredients: ball: water is 1:1.8:0.8, and the prepared raw materials are crushed to make them into fine powder; S13, sieving the fine powder raw material with a magnetic separator to remove iron, and then mixing it with water and repeatedly stirring until a uniform slurry is formed; S14, filtering and kneading the mud and then aging it for later use, the mud fineness is 0.02-0.03% of the residue on the 10,000-hole sieve, and the moisture content of the mud is 23-25%.
3. The method for preparing a pyrophyllite high-grade white porcelain according to claim 1, characterized in that: In step S2, the glaze is prepared according to the formula components, including the following steps: S21, mixing the raw materials for preparing the glaze according to the formula ratio, and crushing and beating the ingredients to obtain a mixture; S22, adding the mixed material in step S21 into a rapid ball mill for mixing and ball milling for 20 hours, and adding an appropriate amount of water, with the ratio of mixed material: ball: water being 1:1.5:0.6, to obtain a ball mill material; S23, adding water to the ball mill to prepare a glaze.
4. The method for preparing a pyrophyllite high-grade white porcelain according to claim 2, characterized in that: In step S3, the clay material in step S14 is poured into a shaping mold, and is formed into a green body by vibration and compression. The formed green body is then trimmed and dried to remove unevenness and defects on the surface of the green body, and to remove excess moisture.
5. The method for preparing a pyrophyllite high-grade white porcelain according to claim 4, characterized in that: In step S4, when the glazing specific gravity is 1.36-1.40, the method of applying the glaze is dipping; when the glazing specific gravity is 1.55-1.60, the method of applying the glaze is spraying. The dried material components are added into a rapid ball mill according to the ratio for mixed ball milling, and the thickness of the glaze layer is 0.3-0.4mm.
6. The method for preparing a pyrophyllite high-grade white porcelain according to claim 5, characterized in that: In step S5, the secondary firing is performed by placing the glaze blank obtained in step S4 in a 74m high-temperature tunnel kiln under oxidizing atmosphere conditions to melt the glaze and adhere to the surface of the porcelain. The maximum firing temperature is 1310°C, the firing cycle is 16h, and the insulation time is 100min.
Citation Information
Patent Citations
High-strength tableware ceramics and preparation technology thereof
CN109020477A
Matt archaized porcelain prepared from ceramic waste and preparation method of matte archaized porcelain
CN114634350A